An innovative cluster in industrial areas of Irkutsk - Shutova, Sofia; Dagdanova, Tsyredar (project baikal, 2021)
The article analyses the possibilities for reconstruction of deserted industrial areas in Irkutsk and arrangement of a scientific, educational and cultural cluster that would meet current town-planning requirements. The article reviews the functions of the cluster, architectural principles of spatial rearrangement and possible conditions for economic growth and settlement of people on the territory of the Irkutsk region.
Keywords: reorganization of industrial areas; innovative cluster; Novo-Lenino; research and educational activity; human potential